(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In the present-day, congestion considers one of the biggest problems experienced by urban areas. This congestion led to form the conflicting movements at intersections, merging, roundabouts, etc. The objective of this study is to investigate the traffic congestion problem at the two selected roundabouts at CBD area in Hilla city. Roundabouts consider safer than the conventional intersections, but it has less capacity than corresponding intersections. In Iraq, several roundabouts were built in the last decade to improve the traffic performance. However, most of these roundabouts are unable to accommodate the rapid growth in traffic volumes and suffer from a serious issue in congestion. Therefore, this study aims to evaluate these roundabouts. The VISSIM simulation software has been used to perform the evaluation analysis for these selected roundabouts. Then, field data have been collected by using two video cameras that installed by using a fabricated equipment. The process of collecting data has lasted for 8 hours at each roundabout. And then, this field data has been used to calibrate the simulation model (VISSIM). After making the required calibration and validation for the simulation model, the developed model was depended to perform the evaluation and find the suitable solution to solve the traffic congestion at these roundabouts.